Zuzug, Fortzug, Umzug — die Stadtregion Bonn in Bewegung - Föbker, Stefanie; Leister, Nina; Temme, Daniela; Wiegandt, Claus-Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
In the framework of demographic change a reduction of population numbers is discussed at present as an important trend in addition to the ageing of society and the increase of persons with a migration background. In addition to shrinking regions which determine the spatial planning policy debate at present, structurally strong regions still exist even today that are characterised by population growth. This also includes the Bonn region. Prognoses show that its population growth will continue also in the future in contrast to numerous other cities and regions in North Rhine-Westphalia.In the article the results of a study on migration flows and migration motives in this growing region are presented. One aim is to demonstrate to what extent social changes have impacts on migration decisions in the framework of demographic change. The results show that migration decisions of the older generation are increasingly characterised by a prospective look towards old age and that the ageing of society has impacts on housing location decisions and on the housing market already today. Furthermore new household forms which develop as a result of the plurality of lifestyles are leading to changed housing requirements. At the same time changed mobility demands are reflected in the selection criteria for the housing location. Finally the creation of ownership also reflects the aspect that one is living in a growing region.